Injection-site reactions from clostridial vaccines: a critical control point? - McFarlane, B.J.; Stokka, Gerald L.; Basaraba, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One 550 lb steer was injected subcutaneously twice, once on each side of the neck, with 5 milliliters of Ultrabac 7 ficlostridial vaccine with a new 16 gauge, 3/4 inch needle. The injections were given 30 days and 36 hours prior to euthanasia, at which time the two resultant lesions were collected. The lesions were evaluated for tissue damage, and physical descriptors were recorded. The 36-hour injection caused an acute lesion with higher than normal levels of neutrophils and erythrocytes in its center. Within the surrounding skeletal muscle, levels of fibrin and edem a fluid were increased, causing separation of the muscle fibers and hemorrhaging. The 30-day injection formed a chronic lesion differing from the 36- hour lesion, primarily by the increased amounts of fibrous connective tissue forming its center. This fibrous connective tissue also extended into surrounding skeletal muscle bundles. The surrounding skeletal muscle also showed signs of degeneration with minimal regeneration. These findings describe the tissue damage that can occur with subcutaneous injection of a clostridial vaccine.
Keywords: Beef; Injection-site; Muscle tissue; Clostridial; Cattle